2022
DOI: 10.1186/s12889-022-14585-9
|View full text |Cite
|
Sign up to set email alerts
|

Health and service utilization among a sample of gender-diverse youth of color: the TRUTH study

Abstract: Background While there is growing research considering the experiences of transgender youth whose identities align with the gender binary, especially among young trans women, there are significantly fewer studies that accurately capture data about nonbinary youth, and even fewer studies capturing the experiences of transgender and gender diverse (TGD) youth of color. The purpose of this research was to assess the prevalence of sexual health behaviors, mental health challenges, substance use, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In contrast, other clinical and non-clinical studies found no evidence for elevated rates of internalizing conditions in non-binary youth compared to binary youth (e.g., Aparicio-García et al, 2018 ; Fontanari et al, 2020 ; Rusow et al, 2022 ; Tordoff et al, 2022 ; Table S1). Furthermore, some studies highlight that there may be differences between AFAB and AMAB non-binary adolescents, highlighting the need to take the birth-assigned sex into account (McKay & Watson, 2020 ; Parodi et al, 2022 ; Rimes et al, 2019 ; Thoma et al, 2019 ).…”
Section: Introductionmentioning
confidence: 83%
“…In contrast, other clinical and non-clinical studies found no evidence for elevated rates of internalizing conditions in non-binary youth compared to binary youth (e.g., Aparicio-García et al, 2018 ; Fontanari et al, 2020 ; Rusow et al, 2022 ; Tordoff et al, 2022 ; Table S1). Furthermore, some studies highlight that there may be differences between AFAB and AMAB non-binary adolescents, highlighting the need to take the birth-assigned sex into account (McKay & Watson, 2020 ; Parodi et al, 2022 ; Rimes et al, 2019 ; Thoma et al, 2019 ).…”
Section: Introductionmentioning
confidence: 83%
“…Within the Transgender Youth of Color Cohort Study, 67% of nonbinary youth assigned female at birth and 65% of transgender men reported condomless sexual interactions in the last 6 months. Despite these rates of condomless sex within the cohort, only 8% had taken PrEP in their lifetime and 3% of participants reported actively taking PrEP [ 17 ]. This underscores the urgent need for interventions that specifically focus on PrEP uptake within SGMY populations.…”
Section: Introductionmentioning
confidence: 99%